ANALISIS SPASIAL PENYAKIT KUSTA DI KOTAMADYA SORONG - , Marjono; , Prof.dr. Hari Kusnanto, DrPH, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Although Indonesia has achieved the step of elimination at national level, there are still several provinces with a high rate of leprosy disease. It can be expected that the elimination of leprosy disease can be achieved at best by making a spatial analysis and mapping on those with the disease and variations in several risk factors for the dissemination. Objective: To find out whether or not there is the clustering of leprosy disease, and to identify relationship between the leprosy disease and social- economic, demographic and geographic factors. Method: The study was an analytical research using a quantitative method with a case-control design assisted by the GIS software. Data analysis was done by using the Satscan and EpiInfo softwares (statcalc), followed-up by multivariate analysis. Result: Most likely cluster occurred with the cluster radius of 5.47 km (Pvalue of 0.042), while secondary cluster occurred with the cluster radius of 4.04 km (P-value of 0.098). The most likely cluster of leprosy divided MB occurred with the radius 34 m, while secondary cluster occurred with radius 17 m. Bivariate analysis